2003
DOI: 10.1053/ejvs.2002.1926
|View full text |Cite
|
Sign up to set email alerts
|

Results of urgent and emergency thoracic procedures treated by endoluminal repair

Abstract: endoluminal repair of thoracic aortic disease requiring urgent/emergency treatment has encouraging results with low morbidity and mortality rates compared with open surgery. Long-term follow-up is required to assess the durability of the grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 27 publications
2
35
0
2
Order By: Relevance
“…Endoluminal repair should reduce the length of stay in intensive care units, high dependency units and in hospital, with an earlier return to activities of daily living and consequent improvement in the quality of life. [63][64][65][66] An additional drainage procedure is usually required either via CT guided drainage or by open surgical approach (Fig. 1a, 1b).…”
Section: Endovascular Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoluminal repair should reduce the length of stay in intensive care units, high dependency units and in hospital, with an earlier return to activities of daily living and consequent improvement in the quality of life. [63][64][65][66] An additional drainage procedure is usually required either via CT guided drainage or by open surgical approach (Fig. 1a, 1b).…”
Section: Endovascular Treatmentmentioning
confidence: 99%
“…When patients present with rupture or have fever, the EVAR method should be considered as a temporary measure to achieve hemodynamic stability. [63][64][65][66][67] Additionally, if the fever persists after the EVAR, This would be an indication to keep the patient on long-term broad-spectrum antibiotics for a long-term until a definite surgical treatment is considered. However, further multi institutional and registry data are required to clarify the long-term outcomes of EVAR and to determine whether EVAR use in infected aortic aneurysms is as effective as or better than standard operation.…”
Section: Endovascular Treatmentmentioning
confidence: 99%
“…Such deaths may be involved with serious clinical and medico-legal consequences related to medical negligence and compensation, which depend on the prognostication of the severity and the proportion of medical negligence if any. Reviews of clinical literature show that a diagnosis was made ante-mortem in most cases, and that early diagnosis can allow ample time for intervention, reducing the mortality [12,15,[19][20][21]. As pointed out by Chen et al [22] the correct diagnosis as soon as possible saves time and hence saves lives.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent results have been reported for commercially available SGs, which have a narrow and flexible delivery system and can be used in emergency cases. [43][44][45][46][47] Although Kato et al 48 have reported the feasibility of EVR using handmade SGs for blunt aortic injury, it is disadvantageous compared with using commercially available SGs because of the time required to produce the SG using 3D-CT scans and angiography, which are conducted prior to the procedure. It is necessary to devise handmade SGs that can be used in emergency cases because then EVR could be used at least as a temporary treatment prior to surgical repair or as a therapeutic alternative in critically ill patients, such as those with ruptured, traumatic, or mycotic aneurysms.…”
Section: Discussionmentioning
confidence: 99%